Spinal Instrumentation in the Setting of Nontuberculous Spondylodiscitis: A Prospective Analysis - Himanshu Prasad; P. V. Satyanarayana Murthy; Vamsi K Varma; A. V. Gurava Reddy (Journal of Orthopedics, Traumatology and Rehabilitation)
Study Design: This was a prospective cohort study. Purpose: The purpose of this study was to evaluate the efficacy of surgical treatment in nontuberculous spondylodiscitis and its effects on the functional and radiological outcomes and define a treatment algorithm. Overview of Literature: Most of the available literature on surgical management of nontuberculous spondylodiscitis is retrospective in nature. A prospective study analyzing functional (Oswestry Disability Index [ODI] and Visual Analog Scale [VAS]) and radiological outcomes of surgical intervention is scanty in the literature. Materials and Methods: A prospective analysis of 22 patients was performed who underwent surgical intervention for biopsy-proven nontuberculous spondylodiscitis. Preoperative ODI and VAS scores were compared with that at 1-year postoperative follow-up. Microbiological details of each patient were noted. Radiological evidence of healing was reported at the final 1-year follow-up. Results: Of 22 patients, 12 were male and the remaining were female, with a ratio of 1.2:1. The average age was 58 years. The most common region of involvement was lumbosacral followed by dorsal and cervical. All the patients underwent single-stage surgery. Microbiological studies showed growth in only 16 patients (72.7%). Staphylococcus aureus was the most common organism isolated. The mean VAS score before surgery was 8.9 which improved to 2.05 at 1-year follow-up. Similarly, the mean ODI score improved from 86.64% to 20.65% at 1-year follow-up with significant P < 0.01. Two patients needed revision for implant loosening. At the final follow-up, all patients had radiological evidence of bony consolidation. Conclusions: The study highlights improved outcomes with surgical intervention combined with appropriate antibiotics. With minimal complication rates, increased stability achieved following surgery alludes to good pain control and hence early mobilization. However, there is a grave concern about culture-negative spondylodiscitis which can lead to poor outcomes. Hence there is a need for further multicentre studies to strategize management of these cases.